Optimalisasi Pelayanan BPJS Ketenagakerjaan Cabang Merauke Dalam Kepesertaan Bukan Penerima Upah (BPU) Pada Sektor Pedagang - Pohan, Farida Romaito; Wibowo, Juventus Bangkit; Kombobiran, Lidia (Jurnal Administrasi Karya Dharma, 2023)
Job security is one of the human rights and rights as a citizen that must be realized by the founding fathers of the Indonesian nation as stated in the 1945 Constitution and Pancasila. According to the main employment status category, workers can be combined into two parts, namely formal workers and informal workers. Formal workers consist of: 1) Workers who try to be assisted by permanent workers/paid workers 2) Laborers/employees/employees Workers who try to be assisted by permanent workers/paid workers. BPJS Ketenagakerjaan offers the Non-Wage Recipient Program (BPU) for informal sector self-employed workers. Because if at any time an accident occurs or causes death, the informal sector self-employed worker who has registered as a participant in the BPU Employment BPJS program and their family will receive benefits or guarantees such as hospital fees and compensation that have been determined according to applicable regulations. The goal to be achieved in this study is the Optimization of Public Services at the Merauke Branch Employment BPJS in non-recipient membership (BPU). The research method used in this study is a qualitative approach. Data collection techniques using observation and interviews. The results of the study show that the Optimization of Services at the Merauke Branch of the Employment BPJS Office is seen from five gaps, namely the Knowledge gap, Standards gap, Deliver. gap, Communication gap, and Service gap. Obstacles and pain were found in the services provided by BPJS Ketenagakerjaan, but they can be overcome by employees who always listen to every mistake experienced by participants properly and explain properly and clearly and in detail to participants so that conflicts that occur in services can be resolved by well and services are running well and safely again and there is a lack of public understanding of the importance of employment guarantees and protection benefits.